PENGARUH HARGA, KUALITAS PRODUK, KUALITAS LAYANAN, TERHADAP KEPUASAN PELANGGAN PADA RUMAH MAKAN BEBEK DAN AYAM GORENG PAK NDUT DI SAMARINDA - Yuni Diah Saraswati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
The problem occurred in Rumah Makan Bebek Pak Ndut based on observations conducted by researchers after conducting interviews to customers showed that customers still feel less satisfied with the price, quality of products and services. The price applied is still at a value less precise by some customers, the quality of the product is less in accordance with the expected and the service that looks less to customers who ask for orders that do not come. This research aims to determine the significance of the effect of price (X1), product quality (X2) and quality of service (X3) partially and simultaneously to customer satisfaction (Y) as well as to know and analyze the most influential customer satisfaction in the Pak Ndut restaurant in Samarinda